A Novel KCNJ13 Nonsense Mutation and Loss of Kir7.1 Channel Function Causes Leber Congenital Amaurosis (LCA16). Issue 7 (20th May 2015) - Pattnaik, Bikash R.; Shahi, Pawan K.; Marino, Meghan J.; Liu, Xinying; York, Nathaniel; Brar, Simran; Chiang, John; Pillers, De‐Ann M.; Traboulsi, Elias I.
<x xml:space="preserve">Abstract</x> We discovered a novel mutation in KCNJ13 gene and report clinical manifestations of LCA16 patient. Using expression of mutant plasmid in CHO‐K1 cells we demonstrate that the truncated mutant protein is non‐functional. In addition, inhibiting Kir7.1 expression in mouse through RNA interference, results in alterations of electroretinogram similar to that found in LCA patients.